Purchasing behavior of female teenagers on vanity products - Sideco, Herkell Kimmi M.; Chua, Consuelo T. (2009.)
The study examined the purchasing behavior of female teenagers on vanity products. Specifically, it described female teenagers' purchase of vanity products in terms of items brought, regularity of purchase and amount spent. It also determined factors that influence the selection of vanity products. A total of 100 female students from two different schools in Metro Manila participated in the study. data were gathered using the researcher-made Vanity Product Purchase Questionnaire. Data were analyzed using descriptive statistics. Results show that teenagers usually purchase vanity products that help maintain their good and proper appearance. Most of the products that are purchased frequently are those that are used daily like astringents & moisturizers for facial products, body lotion and body powder for body products, hair gel and hair spa for hair products and lastly, cologne and perfume for scent products. Majority of teenagers spend less than 40% of their allowance on vanity products. They mostly purchase products that are less than Php 300.00 except for facial products that are usually bought at a higher price. Price and quality are the two most influential factors in purchasing vanity products. Family and peer influence follow; wherein family influence was strong on products used privately while peer influence was strong on products used publicly. Brand and advertisements do not have strong influences on the purchase of vanity products. Recommendations for home economists, consumer educators, entrepreneurs and future researchers are provided at the end of the paper.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Consumer behavior -- Philippines